Drosophila Rtf1 functions in histone methylation, gene expression, and Notch signaling. - Tenney, K.; Gerber, M.; Ilvarsonn, A.; Schneider, J.; Gause, M.; Dorsett, D.; Eissenberg, J.C.; Shilatifard, A. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
The Rtf1 subunit of the Paf1 complex is required for proper monoubiquitination of histone H2B and methylation of histone H3 on lysines 4 (H3K4) and 79 in yeast Saccharomyces cerevisiae. Using RNAi, we examined the role of Rtf1 in histone methylation and gene expression in Drosophila melanogaster. We show that Drosophila Rtf1 (dRtf1) is required for proper gene expression and development. Furthermore, we show that RNAi-mediated reduction of dRtf1 results in a reduction in histone H3K4 trimethylation levels on bulk histones and chromosomes in vivo, indicating that the histone modification pathway via Rtf1 is conserved among yeast, Drosophila, and human. Recently, it was demonstrated that histone H3K4 methylation mediated via the E3 ligase Bre1 is critical for transcription of Notch target genes in Drosophila. Here we demonstrate that the dRtf1 component of the Paf1 complex functions in Notch signaling.